The maternal cervix: Why, when and how? - O'Hara, Sandra; Zelesco, M.; Sun, Zhonghua; Lee, E. (2015)
Introduction: The incidence of preterm birth has continued to rise in most countries in the world during the last decade. There are many clinical risk factors that increase the risk of preterm birth. It has been shown that a sonographically shortened cervical length is a strong indicator of subsequent preterm birth in pregnancy. Background: It has been established that women at an increased risk of preterm birth should have the cervical length recorded using a transvaginal approach. The sensitivity of a shortened cervical length to predict preterm birth is higher in women with a previous preterm birth, with reduced sensitivity in low risk women. The maternal cervix may be assessed using transabdominal, transperineal and transvaginal ultrasound approaches. This article discusses the available research into the use of these differing techniques and current guidelines for measuring maternal cervical length. Summary: Measuring the maternal cervical length has become an important part of the mid trimester morphology examination. The appropriate technique to screen the cervical length in women at low risk of preterm birth is still debatable throughout the wider obstetric and ultrasound communities.